Investigation of improving wear performance of hypereutectic 15%Cr-2%Mo white irons - R. Reda; A. Nofal; Kh. Ibrahim (China Foundry, 2010)
This study aimed at optimizing impact toughness and abrasion wear resistance of 15%Cr-2%Mo hypereutectic abrasion-resistant white irons. The effects of dynamic solidification, niobium addition, combined action of them and heat treatment have been investigated. Investigations were performed by means of the image analyzer, scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS) and X-ray diffraction. Impact toughness and abrasion wear resistance tests were conducted. Fracture and worn surfaces were studied. Results indicated that microstructural control during solidification is the most valuable tool to attain the optimum combination between impact toughness and wear resistance in hypereutectic iron. Combined action of Nb addition and dynamic solidification improves impact toughness and wear resistance even more than the action of each individual factor. In the as-cast condition, impact toughness and abrasion resistance were increased after dynamic solidification compared to statically solidified one by 71.4% and 10%, respectively. This enhancement was increased to 114.3 % and 28.8 % by adding 2% Nb. Lower tempering temperature of 260°C exhibits better impact and abrasion resistance than the sub-critical tempering temperature of 500°C.